Summerdog - Roberts, Thom.; Zabriskie, George Albert, 1926- (New York : Avon Books, 1978)
A family adopts an abandoned dog that proves to be a resoureful detective.
Keywords: Dogs -- Juvenile fiction; Dogs -- Fiction; Mystery and detective stories